2003
DOI: 10.1002/jssc.200301543
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of theophylline, tolbutamide, mephenytoin, debrisoquin, and dapsone in human plasma using high‐speed gradient liquid chromatography/tandem mass spectrometry on a silica‐based monolithic column

Abstract: Simultaneous determination of theophylline, tolbutamide, mephenytoin, debrisoquin, and dapsone in human plasma using high-speed gradient liquid chromatography/tandem mass spectrometry on a silica-based monolithic column Theophylline, tolbutamide, mephenytoin, debrisoquin, and dapsone are marker substrates for CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A4, respectively. A silica-based monolithic column (Chromolith SpeedROD RP-18e, 5064.6 mm) was used to separate these five marker substrates of cytochrome P450 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Warfarin (administered with vitamin K, the pharmacodynamic effect is ablated) was used as a safe and accurate biomarker for CYP2C9 [19]. LC-MS/MS method was validated for theophulline, tolbutamide, mephenytoin, debrisoquin, and dapsone as probes for CYP 1A2, 2C9, 2C19, 2D6, and 3A4 [20]. Depending on the study design, therapeutic area of the drug candidate, potential co-administered medicine, and physician or clinic site's preference, several combinations of cocktails can be employed and not all probes may be included in the in vivo studies if the in vitro data suggested lack of evidence for certain probes.…”
Section: Lc-ms/ms Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Warfarin (administered with vitamin K, the pharmacodynamic effect is ablated) was used as a safe and accurate biomarker for CYP2C9 [19]. LC-MS/MS method was validated for theophulline, tolbutamide, mephenytoin, debrisoquin, and dapsone as probes for CYP 1A2, 2C9, 2C19, 2D6, and 3A4 [20]. Depending on the study design, therapeutic area of the drug candidate, potential co-administered medicine, and physician or clinic site's preference, several combinations of cocktails can be employed and not all probes may be included in the in vivo studies if the in vitro data suggested lack of evidence for certain probes.…”
Section: Lc-ms/ms Methods Developmentmentioning
confidence: 99%
“…Due to its speed, sensitivity, and selectivity, liquid chromatography/tandem mass spectrometry (LC-MS/MS) has become the method of choice for analyzing drug candidates in biofluids [9][10][11]. In vitro metabolic interaction screening assay for determination of marker substrates of CYP450s using N-in-1 approach and LC-MS/MS have been reported earlier [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The use of MS has decreased detection limits to as low as 63 ng/mL for theophylline metabolites. Run times were reduced to under 10 min using LC-MS/MS methods [6][7][8][9][10][11][12][13]. However, all of these methods involved multistep extractions, large volumes of organic solvent, and required intensive labor to prepare the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several papers4–11 have been published regarding the use of monolithic columns for high‐throughput biological sample analysis. The unique biporous structure12–14 of the monolithic column, where small mesopores provide large surface areas for sufficient separation capacity and larger through pores provide considerably reduced back‐pressure at high flow rates, allows high efficiency separation at high flow rates.…”
mentioning
confidence: 99%